2022
DOI: 10.3389/fendo.2022.932343
|View full text |Cite
|
Sign up to set email alerts
|

Common Dietary Modifications in Preclinical Models to Study Skeletal Health

Abstract: Bone is a highly dynamic tissue that undergoes continuous remodeling by bone resorbing osteoclasts and bone forming osteoblasts, a process regulated in large part by osteocytes. Dysregulation of these coupled catabolic and anabolic processes as in the case of menopause, type 2 diabetes mellitus, anorexia nervosa, and chronic kidney disease is known to increase fracture risk. Recent advances in the field of bone cell metabolism and bioenergetics have revealed that maintenance of the skeleton places a high energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…AN is an eating disorder that is characterized by strict restrictions of food intake, leading to abnormally low body weight and an intense fear of gaining weight [12]. While past epidemiological studies have focused on young women in Western countries, anorexia nervosa has been reported in men and women of all ages worldwide.…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
See 2 more Smart Citations
“…AN is an eating disorder that is characterized by strict restrictions of food intake, leading to abnormally low body weight and an intense fear of gaining weight [12]. While past epidemiological studies have focused on young women in Western countries, anorexia nervosa has been reported in men and women of all ages worldwide.…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
“…AN results in a notable reduction in bone mineral density (BMD) in approximately 40% of patients and a three times increased lifetime fracture risk [12]. Another noticeable skeletal phenotype concerning anorexia is the increased number and size of bone marrow adipocytes despite a lipodystrophic response.…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
See 1 more Smart Citation